High Occurrence of Staphylococcus aureus Isolated from Fitness Equipment from Selected Gymnasiums - Lesley, Maurice Bilung; Ahmad Syatir, Tahar; Rosdi, Kira; Aina Ariﬀah, Mohd Rozali; Kasing, Apun (Hindawi Publishing, 2018)
Introduction. Staphylococcus aureus is a leading cause of cutaneous bacterial infection involving community. Methods. In this study, a total of 42 swab samples were collected from the surface of various ﬁtness equipment such as back machines, exercise mats, dip stations, dumbbells, and treadmills. Identiﬁcation of the bacterial isolates was conducted using biochemical tests and further analysed molecularly using the PCR method targeting nuc gene (270bp). The nuc gene encodes for the thermos nuclease enzyme, a virulent factor of S. aureus. Results. The ﬁndings showed 31 out of 42 swab samples (73.81%) were positive with S. aureus. Conclusion. This study showed that gymnasium equipment is a potential reservoir for S. aureus and might play an important role in transmitting the pathogen to humans.